What kind of welfare state is emerging in China? - Stein Ringen; Kinglun Ngok (United Nations Research Institute for Social Development (UNRISD), 2013)
China is joining the group of countries that have reasonably comprehensive systems of social protection in place. In 2010, the National Peoples Congress adopted the first national Social Insurance Law, representing the culmination of a process of radical social reform. The question this paper asks is: what kind of welfare regime is being built in the Peoples Republic of China? China has been politically unique. It is one of only five remaining communist states, the others being Cuba, Laos, the Democratic Peoples Republic of Korea and Vietnam, and the only one (with some qualification for Vietnam) that has been economically successful. The characteristics of a communist state include centralized power in the hands of a party élite and that this élite is presumably motivated, to varying degrees, by some kind of socialist ideology of statism and social justice. While maintaining its political uniqueness, China has shed its economic uniqueness. With the reform and opening up that started in 1978, it turned its back on planned economy isolationism and has adopted an open socialist market economy. In considering what kind of welfare state is emerging in China, the paper looks at two hypotheses: is China producing a welfare state of its own kind, possibly a "socialist" welfare state? Or, if it is reproducing a conventional welfare state, what kind of previous experience elsewhere is it replicating?
Keywords: 330